Destruction of Polyelectrolyte Microcapsules Formed on CaCO3 Microparticles and the Release of a Protein Included by the Adsorption Method - Musin, Egor V.; Kim, Aleksandr L.; Tikhonenko, Sergey A. (Polymers, 2020)
The degradation of polyelectrolyte microcapsules formed on protein-free CaCO3 particles consisting of polyallylamine (PAH) and polystyrene sulfonate (PSS) and the resulting yield of protein in the presence of various salts of different concentrations, as well as at two pH values, was studied by fluorescence spectroscopy; the protein was incorporated into prepared microcapsules by adsorption. It was found that a high concentration of sodium chloride (2 M) leads to considerable dissociation of PAH, which is apparently due to the loosening of polyelectrolytes under the action of ionic strength. At the same time, 0.2 M sodium chloride and ammonium sulfate of the same ionic strength (0.1 M) exert less influence on the amount of dissociated polymer. In the case of ammonium sulfate (0.1 M), the effect is due to the competitive binding of sulfate anions to the amino groups of the polyelectrolyte. However, unlike microcapsules formed on CaCO3 particles containing protein, the dissociation of polyelectrolyte from microcapsules formed on protein-free particles increased with increasing temperature. Apparently, a similar effect is associated with the absence of a distinct shell, which was observed on microcapsules formed on protein-containing CaCO3 particles. The high level of the presence of Fluorescein isothiocyanate (FITC)-labeled Bovine Serum Albumin (BSA) in the supernatant is explained by the large amount of electrostatically bound protein and the absence of a shell that prevents the release of the protein from the microcapsules. In 2 M NaCl, during the observation period, the amount of the released protein did not exceed 70% of the total protein content in the capsules, in control samples, this value does not exceed 8%, which indicates the predominantly electrostatic nature of protein retention in capsules formed on protein-free CaCO3 particles. The increase in protein yield and peeling of PAH with increasing pH is explained by the proximity of pH 7 to the point of charge exchange of the amino group of polyelectrolyte, as a result of the dissociation of the microcapsule.